The ability of the thromboelastogram (TEG® R-time difference between kaolin and heparinase) as a point of care test to predict residual heparin activity after in vitro protamine titration - Joseph, Lauren Ann (Stellenbosch : Stellenbosch University, 2017)
Thesis (MMed)--Stellenbosch University, 2017.